2011
DOI: 10.1007/s10237-011-0295-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of load history in intervertebral disc mechanics and intradiscal pressure generation

Abstract: Solid-fluid interactions play an important role in mediating viscoelastic behaviour of biological tissues. In the intervertebral disc, water content is governed by a number of factors, including age, disease and mechanical loads, leading to changes in stiffness characteristics. We hypothesized that zonal stress distributions depend on load history, or the prior stresses experienced by the disc. To investigate these effects, rat caudal motion segments were subjected to compressive creep biomechanical testing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…13, 18 These models have been valuable in demonstrating significant differences in material properties with loading response, recovery behavior, injury, and degeneration. 11,[19][20][21][22] A diurnal loading cycle includes large compressive loads that are sustained throughout the day and reduced during bed-rest recovery. Previous studies demonstrated that the rate of disc height recovery during unloading is 3 to 4 times slower than the rate of disc height loss during loading, suggesting that passive diffusion of water molecules is not sufficient for full recovery within 8 hours.…”
mentioning
confidence: 99%
“…13, 18 These models have been valuable in demonstrating significant differences in material properties with loading response, recovery behavior, injury, and degeneration. 11,[19][20][21][22] A diurnal loading cycle includes large compressive loads that are sustained throughout the day and reduced during bed-rest recovery. Previous studies demonstrated that the rate of disc height recovery during unloading is 3 to 4 times slower than the rate of disc height loss during loading, suggesting that passive diffusion of water molecules is not sufficient for full recovery within 8 hours.…”
mentioning
confidence: 99%
“…This affects the water-binding capacity, thereby reducing the hydrostatic pressure (Sato et al, 1999), and altering the response to compressive loads (Hwang et al, 2012;Vergroesen et al, 2014). The influence of proteoglycan content on IVD mechanics has been shown indirectly, as enzymatic digestion of proteoglycans, induced by injection of chondroitinase ABC (CABC), caused disc narrowing (Fry et al, 1991;Hoogendoorn et al, 2007;Lü et al, 1997), and changed flexion mechanics (Lü et al, 1997) and intradiscal pressure (Sasaki et al, 2001).…”
Section: Ks Emanuel Et Al Poroelastic Behaviour Of the Degenerating Ivdmentioning
confidence: 99%
“…Other studies used complete motion segments for biomechanical in vitro research, but the IVDs used were removed from their physiological conditions and unloaded for a while, which may have influenced the results of the research performed so far (e.g. Hwang et al, 2012;Wilke et al, 1998). The recent development of animal disc culture systems may benefit research relating degeneration to mechanical function, as they allow extended loading of animal IVDs in order to approximate physiological conditions (Jim et al, 2011;Korecki et al, 2007;Paul et al, 2012).…”
Section: Ks Emanuel Et Al Poroelastic Behaviour Of the Degenerating Ivdmentioning
confidence: 99%
See 2 more Smart Citations